Weak C—H...O and C—H...π hydrogen bonds and π–π stacking interactions in a series of four N′‐[(E)‐(aryl)methylidene]‐N‐methyl‐2‐oxo‐1, 3‐oxazolidine‐4‐carbohydrazides. Issue 8 (7th July 2015) - Nogueira, Thais C. M.; Pinheiro, Alessandra C.; Wardell, James L.; Souza, Marcus V. N. de; Abberley, Jordan P.; Harrison, William T A
<x xml:space="preserve">Abstract</x> Oxazolidin‐2‐ones are widely used as protective groups for 1, 2‐amino alcohols and chiral derivatives are employed as chiral auxiliaries. The crystal structures of four differently substituted oxazolidinecarbohydrazides, namely N′‐[(E)‐benzylidene]‐N‐methyl‐2‐oxo‐1, 3‐oxazolidine‐4‐carbohydrazide, C12H12N3O3, (I), N′‐[(E)‐2‐chlorobenzylidene]‐N‐methyl‐2‐oxo‐1, 3‐oxazolidine‐4‐carbohydrazide, C12H12ClN3O3, (II), (4S)‐N′‐[(E)‐4‐chlorobenzylidene]‐N‐methyl‐2‐oxo‐1, 3‐oxazolidine‐4‐carbohydrazide, C12H12ClN3O3, (III), and (4S)‐N′‐[(E)‐2, 6‐dichlorobenzylidene]‐N, 3‐dimethyl‐2‐oxo‐1, 3‐oxazolidine‐4‐carbohydrazide, C13H13Cl2N3O3, (IV), show that an unexpected mild‐condition racemization from the chiral starting materials has occurred in (I) and (II). In the extended structures, the centrosymmetric phases, which each crystallize with two molecules (A and B) in the asymmetric unit, form A+B dimers linked by pairs of N—H...O hydrogen bonds, albeit with different O‐atom acceptors. One dimer is composed of one molecule with an S configuration for its stereogenic centre and the other with an R configuration, and possesses approximate local inversion symmetry. The other dimer consists of either R, R or S, S pairs and possesses approximate local twofold symmetry. In the chiral structure, N—H...O hydrogen bonds link the molecules into C(5) chains, with adjacent molecules related by a 21 screw axis. A wide variety of weak interactions, including C—H...O, C—H...Cl, C—H...π and π–π stacking interactions, occur in these structures, but there is little conformity between them.